Understanding barriers impeding the deployment of solar-powered cold storage technologies for post-harvest tomato losses reduction: Insights from small-scale farmers in Tanzania - Rutta, Evodius Waziri (Frontiers in Sustainable Food Systems, 2022)
Postharvest food loss remains one of the major food security challenges in Sub-Saharan Africa (Africa). In Tanzania, it is estimated that about 50 percent of fresh tomatoes perish before reaching consumers due to poor post-harvest management. The lack of cold storage facilities is one of the leading causes of massive post-harvest tomato losses, negatively affecting farmers' livelihoods and the sector's economic contribution. For small-scale farmers in off-grid locations, the adoption of solar-powered cold storage technologies has been found to be a potential solution for reducing losses of highly perishable crops such as tomatoes. However, in Tanzania, the deployment of Solar-powered Cold Storage Technologies (SPCSTs) is limited, leaving the vast majority of rural small-scale farmers without access to such facilities. This study examined barriers impeding the deployment and uptake of Solar-powered Cold Storage Technologies in Tanzania. Farmers' perceptions about SPCSTs and constraints limiting their deployment were examined through semi-structured interviews and Focus Group Discussions (FGD) held between April and June 2021 in Kilolo district, Southeast Tanzania. Participants involved fifty-two (n = 52) small-scale tomato farmers and twenty-three (n = 23) experts and key informants from government and non-profit organizations that were purposively selected. The results show that the deployment of solar-powered cold storage technologies is constrained by limited awareness, high investment costs, low-paying capacity among farmers, and consumer preference for non-refrigerated foods. Addressing these barriers demand promoting policies and programs that attract and retain investment in cold storage technologies and improve SPCSTs affordability through flexible payment arrangements.